24 Body composition is associated with physical capacity and cardiac function in renal transplant recipients. (13th October 2015) - Neale, J; Richler-Potts, D; Highton, P; Smith, AC; Bishop, NC
Abstract : Receiving a kidney transplant can transform the health and quality of life of a patient with end stage renal failure. However, physical function (PF) tends not to recover fully and physical activity levels usually fail to reach that of the general population. Paradoxically, in the post-transplantation period, body composition shifts continuously towards fat tissue, with low muscle mass partly due to immunosuppressive drugs. Cardiovascular (CV) disease remains the major cause of morbidity and mortality. This study aimed to explore the association of PF with cardiac parameters and body composition in RTRs. 35 stable RTRs (Mean age 52 y (range 29–70), 66% male) participated. PF was assessed using sit to stand 5 (STS5) and incremental and endurance shuttle-walk tests (ISWT and ESWT). Cardiac haemodynamic function was measured by bioreactance (NICOM), and body composition by dual energy X-ray absorptiometry (DEXA). Mean body fat%[SEM] was 33[2] and fat-free mass was 51.2 kg [2.0]. ISWT and ESWT inversely correlated, and STS-5 positively correlated, with body fat% (ISWT: r = –0.63; ESWT: r = –0.57; STS-5: r = 0.61, all p < 0.001). Fat-free mass correlated inversely with total peripheral resistance (r = –0.65 p < 0.001) and positively with cardiac output (r = 0.75) and stroke volume (r = 0.79, both p < 0.001). The observed significant correlations between physical function and body fat% strongly support a role for exercise rehabilitation to improve both physical function and body composition in RTRs. An increase in fat-free mass was significantly associated with an improvement in cardiac indices, suggesting that improving muscle mass via exercise, rather than simply losing fat, may help to reduce the risk of cardiac-related morbidity and mortality in this vulnerable population.